Identifikasi Pola Psikologi Komunikasi Resisten dalam Masyarakat - Wahyuni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
The theme of resistance or resistance becomes something of interest to social scientists. In the late 1980s, resistance became a trend in examining cases that were easily observable and empirical. For social researchers, resistance is regarded as cultural, because it arises through the expression and daily actions of society. Analysis of own resistance to a phenomenon many see the things that exist in the daily life of the form of stories, themes of conversation, swearing, and praise the praise and other behaviors so that resistance becomes tit for tat in social scholarship. Attitude is one of the main concept of concern in the science of social psychology. Attitude is also an internal / subjective evaluation process that takes place within a person and can not be observed directly, but can be seen if the attitude has been realized into behavior